Pengaruh Advertising Dan Public Relation Terhadap Keputusan Mahasiswa Memilih Kampus Unisma, Melalui Citra Institusi Kampus Sebagai Variabel Intervening - Khoirul Anam; Rois Arifin; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT In this study aims to determine the effect of Advertising and public relations on the decision of students to choose Unisma campus, through the image of campus institutions as an intervening variable. For the independent variables in this study are Advertising and Public relations, while the dependent variable for this research is the image of the campus institution and the decision to choose. For this type of research using empirical research which uses secondary data, obtained from the Unisma Malang campus (Source BAAK 2019 student data), and primary data obtained from questionnaire collection from each of the respondents that have been previously determined. The population in this study was the class of 2019 students, totaling 3,434 students. which has been determined with a total sample of 97 samples. This sampling technique uses purposive sampling in which proportional sampling has each criterion. To solve the problem in this study using the test instrument which the Validity and Reliability Test, Normality, Path analyst, Hypothesis Test and Sobel Test the test results of the analysis data show that: Advertising, public relations have a positive effect on the image of campus institutions and Advertising, public relation has a significant indirect effect on the decision to vote through the image of the campus institution as an intervening variable. Keywords: Advertising, public relations, image of campus institutions, decision to choose.